IMPLEMENTASI SUPERVISI AKADEMIK - Yosepha, Sr. Tanti; Chiar, H.M; Wahyudi, Wahyudi (Universitas Tanjungpura, 2022)
AbstractAcademic supervision is designed for helping and guiding teachers to improvethe learning system in the classroom. The purpose of this research is to obtainthe accurate information about the Implementation of Academic Supervision atSekolah Kristen Immanuel II Sungai Raya. A qualitative approach with adescriptive case study method is applied in the research. The research